 Mathematics
29 August, 08:35

# 20.Solve the system.3x + y = - 66.2 + 5y = 6

+3
1. 29 August, 09:03
0
The first one 3x + y = - 6

First 3x + y = - 6

-3 - 3x

--. - -

y = - 3x-6

Second 6.2 + 5y = 6

-6.2. - 6.2

--- - - --

5y = - 0.2

- - - --

5. 5

y = - 0.2/5 or - 0.04 as decimal
2. 29 August, 10:24
0
Answer: x = - 1.9867 and y = - 0.0399

Step-by-step explanation: What we have here is a pair of simultaneous equations which are;

3x + y = - 6 - - - (1)

6.2 + 5y = 6 - - - (2)

From equation (1), we shall make y the subject of the equation. So, let

y = - 6 - 3x

Substitute for the value of y into equation (2)

6.2 + 5 (-6 - 3x) = 6

6.2 - 30 - 15x = 6

Collecting like terms we now have

6.2 - 30 - 6 = 15x

Remember that when a negative value crosses to the other side of an equation it becomes positive and vice versa

-29.8 = 15x

Divide both sides of the equation by 15

x = - 1.9867

We can now substitute for the value of x into equation (1)

3x + y = - 6

3 (-1.9867) + y = - 6

-5.9601 + y = - 6

By collecting like terms we now have

y = - 6 + 5.9601

y = - 0.0399.

Hence x = - 1.9867 and y = - 0.0399